A conceptual framework for the development of intelligent, learning style- and computer-based educational software for topics from operations research - Du Plessis, S. A. (Sameul Altenstadt) (Stellenbosch : Stellenbosch University, 2012)
Thesis (PhD)--University of Stellenbosch, 1999